Comparing targeted thrust manipulation with general thrust manipulation in patients with low back pain. A general approach is as effective as a specific one. A randomised controlled trial - Christopher J McCarthy; Louise Potter; Jackie A Oldham (BMJ Open Sport & Exercise Medicine, 2019)
Background Spinal manipulation is commonly used to treat back pain. The application of spinal manipulation has traditionally involved an element of targeting the technique to a level of the spine where the proposed movement dysfunction is sited. We evaluated the effects of a targeted manipulative thrust versus a thrust applied generally to the lumbar region.Methods A randomised controlled clinical trial in patients with low back pain following CONSORT (Consolidated Standards of Reporting Trials) guidelines. Sixty subjects were randomly allocated to two groups: one group received a targeted manipulative thrust (n=29) and the other a general manipulation thrust (GT) (n=31) to the lumbar spine. Thrust was either localised to a clinician-defined symptomatic spinal level or an equal force was applied through the whole lumbosacral region. We measured pressure-pain thresholds (PPTs) using algometry and muscle activity (magnitude of stretch reflex) via surface electromyography. Numerical ratings of pain and Oswestry Disability Index scores were collected.Results Repeated measures of analysis of covariance revealed no between-group differences in self-reported pain or PPT for any of the muscles studied.Summary A GT procedure—applied without any specific targeting—was as effective in reducing participants’ pain scores as targeted approaches.Trial registration number ISRCTN11994230.